Choice-making and choose-ables: making decision agents more human and choosy - Dodd, Lorraine (Springer, 2019)
This paper discusses concepts that might shape, extend, limit or re-focus an agent’s set of options that can then be thought of as that particular agent’s potential in terms of their ways forward and degrees of freedom. Because there is no unambiguous word that conveys the meaning of this higher order concept of choice-making, the term “choose-able” has been adopted in order to distinguish it from the usual decision concepts known as choice or option. An agent’s choose-ables are defined as the imagined deemed possible ways forward, that the agent has to construct, compose or create before they can choose. The central concept of a choose-able is a very powerful one if only it could be surfaced and made explicit. It is often only possible to make inferences about the nature of choose-ables after observing the actions taken once a choice has been made. Drama theory formally develops this kind of inferencing and provided a foundation for this paper as it explores the relational realms of options. The paper presents a funnelling construct and then draws together Catastrophe theory and Culture theory to offer new ways of analysing the shaping effects of relational contexts on an agent’s choose-ables that then act as a medium through which agents are drawn to make choices and carry out observable actions. The strength of the combination of the theories lies in their descriptive power of subjective, relational concepts that hitherto have tended to remain hidden and tacit.
Keywords: Decision options; Choice; Catastrophe theory; Culture theory